Cover JGEET Vol 03 No 02 2018 - (J. Geoscience Eng. Environ. Technol.), JGEET (Journal of Geoscience, Engineering, Environment, and Technology, 2018)
This Volume Consists of Research Article as follow: Structural Analysis of Northwest Sabah Basin by 2D Reconstruction of Seismic Sections Structure and Tectonic Reconstruction of Bayah Complex Area, Banten The Adsorption and Regeneration of Natural Pumice as Low-Cost Adsorbent for Nitrate Removal From Water Macerals Analysis Seam M2 Muaraenim Formation, : Implication Toward Coal Facies and Coal Rank in Kendi Hill, South Sumatra Estimation Microporosity Value of Fontanebleau Sandstone Using Digital Rock Physics Approach A Study on influence of organic ligands on migration of heavy metals through compacted clayey soil Characteristics of Coal and Cleat Attributes in Ulak Lebar and Surroundings Area, Lahat Regency, South Sumatra Lithofacies And Depositional Analysis Environment Of West Section Kolok Nan Tuo Village, Sawahlunto City, West Of Sumatera Geology Of Tanjung Medan ,Rokan IV Koto , Rokan Hulu District, Riau Province